2014
DOI: 10.3354/ame01703
|View full text |Cite
|
Sign up to set email alerts
|

Marine bacterial, archaeal and eukaryotic diversity and community structure on the continental shelf of the western Antarctic Peninsula

Abstract: The classic view of polar ocean foodwebs emphasizes large predators sustained by energy and material flow through short, efficient diatom−krill−predator food chains. Bacterial activity is generally low in cold polar waters compared to that at lower latitudes. This view appears to be changing, with new studies of microbial foodwebs in Arctic and Antarctic oceans. We characterized bacterial, archaeal, and eukaryotic community diversity and composition from 2 depths (near surface and below the euphotic zone) at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
66
2
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 70 publications
(62 reference statements)
17
66
2
14
Order By: Relevance
“…Previous studies of temperate systems have also reported richness maxima in the winter and minima in the summer (Gilbert et al, 2012; Ladau et al, 2013). Similar seasonal trends in bacterial OTU richness have been reported in Antarctic waters (Murray and Grzymski, 2007; Ghiglione and Murray, 2012; Grzymski et al, 2012; Luria et al, 2014). Gilbert et al (2012) observed relatively gradual changes, reporting that day length and serial day alone explained over 66% of the observed variance in richness during a 6-year time series study of the English Channel.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies of temperate systems have also reported richness maxima in the winter and minima in the summer (Gilbert et al, 2012; Ladau et al, 2013). Similar seasonal trends in bacterial OTU richness have been reported in Antarctic waters (Murray and Grzymski, 2007; Ghiglione and Murray, 2012; Grzymski et al, 2012; Luria et al, 2014). Gilbert et al (2012) observed relatively gradual changes, reporting that day length and serial day alone explained over 66% of the observed variance in richness during a 6-year time series study of the English Channel.…”
Section: Discussionsupporting
confidence: 83%
“…Previous analyses in the WAP, based either on community fingerprinting techniques (i.e., denaturing gradient gel electrophoresis) over one or more seasons, or on high-throughput DNA sequencing from only few mid-winter and mid-summer sampling dates, hint at a relationship between bacterial community succession and phytoplankton blooms similar to that observed in more temperate regions (Murray et al, 1998; Murray and Grzymski, 2007; Grzymski et al, 2012; Luria et al, 2014). However, the intervening time period between winter and summer is severely under-sampled in the WAP, as it is throughout the Southern Ocean, making comparisons to other systems difficult.…”
Section: Introductionmentioning
confidence: 96%
“…on a variety of processes, including bacterial responses to environmental gradients, coupling with phytoplankton, and community structures (e.g., Morán et al, 2001;Morán and Estrada, 2002;Ducklow et al, 2012;Luria et al, 2014Luria et al, , 2016Nikrad et al, 2014;Bowman and Ducklow, 2015). However, these studies are mostly short-term and usually constrained to just 1 or 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions favor bacteria capable of an autotrophic lifestyle (Alonso-Sáez et al 2010;Grzymski et al 2012), such as the sulfur-oxidizing gammaproteobacterial clades SUP05 (Marshall and Morris 2013), the closely related clade Arctic96B-1, and the (putatively) OMZ-associated clade ZA2333c (Wright et al 2012). The abundance of Sva0853 and SUP05, typically associated with deeper waters (Shi et al 2010;Kim et al 2013), suggests upwelling or the colonization of carbon-poor surface waters by deep clades during winter, a phenomenon observed elsewhere in Antarctica (Luria et al 2014;Bowman and Ducklow 2015). Although all of these clades were present within frost flowers, they were present at lower abundance than in seawater.…”
Section: Discussionmentioning
confidence: 96%